1996
DOI: 10.1016/0921-4534(96)00055-x
|View full text |Cite
|
Sign up to set email alerts
|

Cathodoluminescence microscopy of superconducting and non-superconducting Tl2Ba2CuO6+δ polycrystals

Abstract: of superconducting and non-superconducting Tl2Ba2CuO6+x polycrystals. Physica C: Superconductivity and its Applications, Elsevier, 1996, 259, pp.121-130. <10.1016 HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers.L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt età la dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1996
1996
1997
1997

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Spectra recorded from the luminescent, plastically deformed areas surrounding the indentations, showed a clear increase of the 2.4eV band relative to the 2.8eV emission. An enhancement of the green CL emission has also been observed in the spectra recorded from polished T12Ba2CuO6+6 ceramics [16].…”
Section: Discussionmentioning
confidence: 99%
“…Spectra recorded from the luminescent, plastically deformed areas surrounding the indentations, showed a clear increase of the 2.4eV band relative to the 2.8eV emission. An enhancement of the green CL emission has also been observed in the spectra recorded from polished T12Ba2CuO6+6 ceramics [16].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous work [21] performed with the same set of samples used here, it was concluded that the CL intensity distribution is not due to impurity phases. This conclusion was obtained from characterization studies regarding kinds and amounts of impurity phases.…”
Section: Discussionmentioning
confidence: 62%
“…SEE and CL can provide complementary information on the defect structure in the oxygen sublattice of TBCO. The CL properties of TBCO have been previously discussed [14,21] and compared with similar results concerning other high-T c superconductors. On the other hand SEE results on TBCO samples have not been, to our knowledge, previously reported.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…3). The 540 nm band, whose formation also involves a contribution from oxygen vacancies, 3,22 is very pronounced in the spectrum of the intermediate zone and is weaker in the spectrum of the peripheral zone. A reduction in oxygen content near the irradiated zone has also been observed by Raman scattering.…”
Section: Resultsmentioning
confidence: 99%